Sorption of Zn(II) and Cu(II) by four Argentinean soils as affected by pH, oxides, organic matter and clay content - Fernandez, Mariela Alejandra (2015)
Increasing heavy metal applications to agricultural soils in the form of phosphatic fertilizers and/or atmospheric deposition have led to extensive research on the chemistry of Zn and Cu in soils. Cu(II) and Zn(II) sorption onto different soil fractions of three Mollisols and one Entisol from the southwest of Buenos Aires Province, Argentina, was studied. Different variables affecting the sorption capacity such as pH, cation exchange capacity, specific surface area (SSA), type and amount of clay minerals present, content of Fe-, Al-, and Mn-oxides and oxohydroxides, organic matter and electric charge parameters were investigated. To assess the monometal sorption, batch equilibrium experiments were performed using Cu(II) and Zn(II) metal solutions over a pH range from 4.0 to 7.0. The increase in metal sorption with increasing pH for both metal cations was attributed to an increase in the negative surface charges. At pH 5.0, Cu(II) showed more affinity than Zn(II) for reactive surface soil sites. Removal of organic matter via H2O2 treatment (<2-mm OMR fraction) dramatically decreased the sorption of both cations; however, Cu(II) was sorbed more than Zn(II). The variation in SSA (obtained by water vapor adsorption) in <2-µm (clay fraction) and <2-mm (whole soil fraction) after Zn(II)/Cu(II) sorption at pH 4 and 6 reflected a different interaction between both cations and binding surface sites. Sorption isotherms correlated better with Langmuir than Freundlich equations. Sorption capacities (qmax) in <2-µm fraction, ranged from 166 to 111 mmol kg−1 for Cu(II), and from 62 to 31 mmol kg−1 for Zn(II). This study extends the understanding of the sorption mechanisms of Cu(II) and Zn(II) to agricultural soils from the semi-arid Pampean region of Argentina. An understanding of the local soil environment is important in order to reduce or prevent contamination of this valuable resource, especially from fertilizers and other such anthropogenic additions to the soil.